(untitled) (Research, Society and Development, 2022)
This study of qualitative nature consists of a bibliographic research based on a Systematic Literature Review (SLR). Its purpose is to analyze how studies published in Brazil in the period within 2010 and the first quarter of 2022 discuss reading and writing acquisition by deaf children. The analysis is supported by a theoretical framework focusing on the education of the deaf, sign language and bilingual education. It covers a total of 47 scientific papers published in national journals and available in SCIELO and CAPES databases on the period mentioned previously. The study intends to answer the following questions, “How is bilingual education of the deaf being understood in Brazil?” and “What is the role of Brazilian Sign Language (Libras) in the literacy process of deaf children?”. It was possible to identify four conceptions of bilingual education, in addition to different compositions of the teaching staff and different possibilities for the bilingual and the inclusive schools. It was also possible to notice that the studies analyzed have something in common: the importance attributed to Libras and how that is articulated in the second language acquisition process for the deaf. The authors of this study point out the need to promote more discussions about the education for the deaf and that this topic should be disseminated and studied more, not only by deaf people or those who work with the deaf, but involving other professionals who contribute and work in education.